Teaching English Oral Expressionand Listening Comprehension at the Department ofLetters and English Language, University of Constantine 1: Past and Present Ups and Downs - BEGHOUL, Youcef (Journal of Human Sciences, 2016)
This paper gives an overview of how Oral Expression and Listening Comprehension have been taught at the Department of English, University of Constantine, ever since the early eighties to the present time in the new LMD system. It provides a critical analysis of the official syllabi of the classical system and that suggested in the current LMDsystem. Then, it contrasts them with the reality of such teaching at the department. This analysis helps determine the shortcomings of each of the two systems. It also suggests some solutions for a more practical teaching of these two crucial skills in a pedagogical context characterized by ever decreasing linguistic and cultural levels and more and more overcrowded classes.